6 - ‘Up as a Rabbit, Down as a Lion’: Socio-economic Determinants of New Idioms of Power – Visual Case Stories from Urban Adamaoua, Cameroon - Holtedahl, Lisbet (Africa Development, 2021)
In the 1990s, I felt empathy with the Sultan of Adamaoua. I do feel empa- thy with one of the richest and most influential industrialists in Cameroon today - emotions which are difficult to convey in today’s Norway. Ideas about Africa, about poverty, corruption, etc. make such feelings politi- cally incorrect. My anthropological research is supposed to lead to posi- tive consequences for the people with whom I work. They be ‘small’ or ‘big’ people. This is called applied research. My research experience has made me conclude the following: Research should contribute to giving people new voices in new arenas; make them visible in new social spheres. I wish for instance, that my research may promote authorities’ listening more to and seeing people who are poor or who are uneducated, and, that their decisions may reach them, empower them. Often, also, one thinks that empowerment only concerns people without power. Since I have for long worked with people with big power, my research should enable their voices to become strengthened and make them visible on the new social arenas that are under pressure from their own behaviour and entrepre- neurship, but that they themselves do not see. What criteria do we use when we decide whether our research should empower people in power? It is important that we include the ‘small’ as well as the ‘big’ in our applied research. Otherwise, democracy can not be promoted.